2012
DOI: 10.4103/2230-8210.93738
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and gonadal dysfunction in chronic kidney disease: Pathophysiology

Abstract: Sexual and gonadal dysfunction/infertility are quite common in patients with chronic kidney disease. Forty percent of male and 55% of female dialysis patients do not achieve orgasm. The pathophysiology of gonadal dysfunction is multifactorial. It is usually a combination of psychological, physiological, and other comorbid factors. Erectile dysfunction in males is mainly due to arterial factors, venous leakage, psychological factors, neurogenic factors, endocrine factors, and drugs. Sexual dysfunction in female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 45 publications
0
67
0
4
Order By: Relevance
“…Abnormalities anywhere along the neurovascular pathway can result in ED -the hypothalamic-pituitary-gonadal axis, vascular supply, and penile tissue damage from either infections or trauma. 13 Psychological factors such as fatigue, stress, and depression may result from chronic illness and contribute further to the development of ED.…”
Section: Male Sexual Dysfunction In Ckdmentioning
confidence: 99%
“…Abnormalities anywhere along the neurovascular pathway can result in ED -the hypothalamic-pituitary-gonadal axis, vascular supply, and penile tissue damage from either infections or trauma. 13 Psychological factors such as fatigue, stress, and depression may result from chronic illness and contribute further to the development of ED.…”
Section: Male Sexual Dysfunction In Ckdmentioning
confidence: 99%
“…The reason for infertility is due to disturbed pulsatile secretion of GnRH, which may be associated with high follicle-stimulating hormone (FSH), luteinizing hormone (LH) and prolactin levels [1]. These hormonal disturbances can reverse after transplant, resulting in normal ovulatory cycles and regular menstruation [4,5]. However, female patients with chronic kidney disease may develop early menopause, 4.5 years earlier than general population [6].…”
Section: Discussionmentioning
confidence: 99%
“…Mejía-Rodríguez et al found that bromocriptine treatment in patients with left-ventricular hypertrophy and end-stage renal disease on peritoneal dialysis decreased left-ventricular mass [97]. Symptomatic hyperprolactinemia in patients with chronic kidney disease can be treated with DA [98]. In currently available literature no clear recommendations regarding treatment of hyperprolactinemia in liver diseases exists.…”
Section: Management Of Other Causes Of Hyperprolactinemiamentioning
confidence: 99%